Characterization of major elements, heavy metals, and rare earth elements in soils of MARDI station at Cameron Highlands, Malaysia using neutron activation analysis - Ashraf, Ahmadreza (2011)
The present thesis reports on the result of an investigation of elemental concentrations present within the topsoil and the granitic bedrock of MARDI Station, Cameron Highlands. The elemental concentrations had been obtained by using instrumental neutron activation analysis which was done at the nuclear reactor of the Instrumental Technology Division, Nuclear Agency of Malaysia (MINT), Bangi. All together there are 34 elements that had been identified, which includes Cr, Zn, K, Mg, Mn, Na, Al, Rb, Ca, Br, Ta, Co, V, Ti, Ba, Ga, Sb, As, Fe, Hf, Cs, Th, U, Zr, Sm, Ce, Eu, La, Lu, Sc, Yb, Nd, Tb, and Dy. The research work begins by establishing the applicability and the accuracy of the technique by analyzing the standard certified reference materials IAEA-Soil-7 and IAEA-SL-1 and also the two multi-element certified standard solutions PTS15 and PTS16 which were provided by International Atomic Energy Agency (IAEA), Vienna, Austria. The concentrations of the elements as obtained by the facility in MINT were compared to the established published values given by IAEA, Vienna. The accuracy of the results as obtained by MINT facilities are comparable to that values published by IAEA, Vienna. Hence, the method was proven acceptable. After the accuracy of the method was established, the concentration of the various elements present within the top soil of MARDI Station and also within the granitic bedrock from which the soil was derived was determined. Four samples from each station were used to ensure repeatability and accuracy. The result on the concentration of the elements obtained by the present research were compared to the result of similar work within Malaysia and internationally. To achieve the objective of the present work, the concentrations of the elements found in the top soil of MARDI Station were compared to the concentration of the same elements found in the granitic bed rock, their enrichment factors were calculated, geoaccumulation index of each element at each station were computed to assess the level of pollution due to each element based on Müller’s criteria. The level of pollution due to each element had also been compared to the target value and intervention value of the Dutch Standard for Soil. Based on the present research and using the Dutch Standard as a guide, it was found that the top soil of MARDI Station in Cameron Highlands does not have the concentrations of elements in excess of the intervention concentration, except only for Th. Thus it can be concluded that the top soil are not polluted by major, minor, heavy metal, trace elements or actinides except for Thorium. The result of the present investigation also shows that certain elements had been introduced anthropogenically into the top soil of MARDI station at certain locations. The anthropogenicity of the elements had been assessed using Kolmogorov-Smirnov tests and box plot tests. The anthropogenity of the elements had been tested at 95% confidence level. The stations which show anthropogenic inputs of pollutants are at M1, M2, M8, M9, M10, M12, M13, M14 and M15. Different suite of elements which includes Al, Cs, Th, Lu, Fe, Ta, K, Tb, Sb, Ca, Sm, Nd, Eu, Dy, Ga, Br and Sb were introduced at different stations within the top soil of MARDI Station. However, the concentrations of these elements do not exceed the intervention values as stipulated by the Dutch Soil Standard, except for Th.